EXPOSURE TO THE PHYSICAL CONDITIONS OF THE HOME ENVIRONMENT WITH PULMONARY TB DISEASE IN KALUMATA VILLAGE: Paparan Kondisi Fisik Lingkungan Rumah dengan Penyakit TB Paru di Kelurahan Kalumata - Washliyah, Siti; Sidebang, Purnama (Jurnal Berkala Epidemiologi, 2024)
Background: Pulmonary TB is included in the ten highest disease categories yearly in almost all health centers in Ternate City, North Maluku. In certain age groups, pulmonary TB can be a cause of death. Environmental factors, especially the physical environment of the house, can be determinants of pulmonary TB disease. Purpose: This study aimed to determine the incidence of pulmonary TB if exposed to the physical environment of the house and the home environment. Methods: This research is observational with a case-control study design. She was held in the Coastal Area of ​​Kalumata Village, Ternate City. The number of samples in this study were all pulmonary TB sufferers. Data were collected from observations, interviews, and measurements to determine exposure to the physical environment of the house and the incidence of pulmonary TB. The chi-square test is used to determine the relationship between the variables studied. Results: The study's statistical results showed that all the variables did not significantly relate to the incidence of pulmonary tuberculosis associated with the physical condition of the house (p-value = 1.00 (> ɑ = 0.05). Conclusion: There is no relationship between the incidence of pulmonary TB and the house's physical condition.